2012
DOI: 10.5539/gjhs.v4n4p149
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Attitudes towards and Comfort about Teaching School-Based Sexuality Education in Urban and Rural Tanzania

Abstract: Teachers’ attitudes towards sexuality education are among the important predictors of their willingness to teach sexuality education programmes in schools. While there is a plethora of studies on teachers’ attitudes towards sexuality in developed countries, there is a paucity of such studies in sub-Saharan Africa in general and Tanzania in particular. This study examined teachers’ attitudes towards and comfort in teaching sexuality education in rural and urban Tanzania. The results show that an overwhelming ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 12 publications
(15 reference statements)
3
34
0
6
Order By: Relevance
“…The inadequate implementation of sexual health education in school is due to various factors, including social and cultural attitudes that do not allow open discussion and teachers’ resistance to teaching sexual health matters [ 14 ]. Furthermore, the existing, widely employed traditional teaching methods do not support the effective delivery of sexual health education [ 13 , 18 ]. Adequately accessible sexual health education could help to protect adolescents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inadequate implementation of sexual health education in school is due to various factors, including social and cultural attitudes that do not allow open discussion and teachers’ resistance to teaching sexual health matters [ 14 ]. Furthermore, the existing, widely employed traditional teaching methods do not support the effective delivery of sexual health education [ 13 , 18 ]. Adequately accessible sexual health education could help to protect adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…Given the reported ineffectiveness of national sexual health education [ 18 , 54 ] and the advances and success of GBL and gamification pedagogies [ 13 ], we aimed to investigate the extent to which GBL and gamification could improve the teaching of sexual health education to secondary school adolescent students. To determine the effectiveness of these methods when compared with the traditional teaching method, we aimed to determine learning performance through sexual health literacy tests and assess students’ Motivation, Attitudes, Knowledge gain, and Engagement using the MAKE model [ 55 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, teachers face challenges in addressing key topics such as condom use, which may be associated with promiscuity [ 27 ]. They may also be uncomfortable discussing subjects like unwanted pregnancies, sexual orientation, masturbation, and contraception [ 24 , 28 ]. Teachers’ attitudes towards adolescent sexual health education are likely to influence the transfer of sexual reproductive knowledge [ 27 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Literature indicates that teachers often report that they are poorly trained in teaching sexual education programs, and thus unable to answer the questions raised in class (Rodriguez, Young, Renfro, Ascencio, Haffner, 1996;Howard-Barr, Rienzo, Pigg & James, 2005). In a research conducted on a group of teachers from Tanzania, it was found that positive attitudes towards teaching sexual education in schools was not enough and that it was necessary to provide teachers with knowledge, skills and confidence in teaching subjects of sexual education (Mkumbo, 2012). In another study on 68 teachers, Gonzalez-Acquaro & College (2009), showed that providing information on sexual education and intellectual disability to teachers increases not only the level of knowledge, but also the attitudes and feelings of self-efficacy.…”
Section: Attitudes Of Special Education Teachers Towards the Sexual Ementioning
confidence: 99%
“…It is commonly acknowledged in the international literature that, in the implementation of SexEd programs, the attitudes of specialists towards sexuality and the way of teaching sexual health topics for people with disabilities might represent a crucial factor related to the effectiveness of these programs (Cohen, Sears, Byers, & Weaver, 2004;Mkumbo, 2012). Also, it is important to take into account the fact that for those children and young people with disabilities that are spending the majority of their time in special education institutions their in-service teachers are sometimes the most accessible source of information about sexuality.…”
Section: Introductionmentioning
confidence: 99%